2020
DOI: 10.1007/s00442-020-04711-y
|View full text |Cite
|
Sign up to set email alerts
|

Experimental drought indirectly enhances the individual performance and the abundance of an invasive annual weed

Abstract: During environmental change, invasive species may be favored by increased resource input or reduced resource use of the resident community. Plasticity in certain plant traits of invasive species may be one possible mechanism behind their ability to quickly exploit unused resources. We tested whether rainfall manipulations (severe drought, moderate drought, watering) alter the growth and reproductive success of the invasive annual Conyza canadensis, and if it translates into a change in the abundance of the spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 63 publications
1
12
0
4
Order By: Relevance
“…In our experiment, competition from corn plants may have limited the availability of light and/or nutrients to burcucumber in the no-drought treatment but had a weaker impact in the drought treatment. A similar explanation was proposed by Mojzes et al (2020), who suggested that horseweed [Conyza canadensis (L.) Cronquist] exhibited improved performance in drought plots because the drought stress alleviated competitive pressure from perennial grasses. However, we cannot explain why corn yield losses due to drought were stronger in the first study year but the effect of drought on burcucumber biomass was similar between years.…”
Section: Silage Corn Yield and Burcucumber Biomasssupporting
confidence: 61%
“…In our experiment, competition from corn plants may have limited the availability of light and/or nutrients to burcucumber in the no-drought treatment but had a weaker impact in the drought treatment. A similar explanation was proposed by Mojzes et al (2020), who suggested that horseweed [Conyza canadensis (L.) Cronquist] exhibited improved performance in drought plots because the drought stress alleviated competitive pressure from perennial grasses. However, we cannot explain why corn yield losses due to drought were stronger in the first study year but the effect of drought on burcucumber biomass was similar between years.…”
Section: Silage Corn Yield and Burcucumber Biomasssupporting
confidence: 61%
“…Estos resultados indicarían que la especie exótica invasora fue más afectada por el estrés hídrico que las gramíneas nativas seleccionadas, al menos en las condiciones experimentales del presente trabajo. Si bien existen estudios que muestran a las especies exóticas invasoras como más exitosas que las nativas en situaciones estresantes (Dukes and Mooney 1999;Mojzes et al 2020;Welles and Funk 2021), también hay trabajos que destacan la gran tolerancia de las nativas, sobre todo debido a una posible adaptación a períodos adversos que ocurren naturalmente en su ambiente (Hobbs and Huenneke 1992;Alpert et al 2000;Funk and Vitousek 2007). Por lo tanto, en la literatura se encuentran resultados contrastantes (e.g., Rejmanek and Richardson 1996;Funk and Zachari 2010;Han et al 2012), lo cual señala que las respuestas de las especies nativas y exóticas invasoras en condiciones de escasez de recursos pueden ser un fenómeno contexto-dependiente y de difícil generalización (Gioria and Osborne 2014).…”
Section: D��������unclassified
“…Similarly, Mojzes et al (2020) showed that drought increased the performance of the invasive Conyza canadensis by decreasing the abundance, and thus competitive effect, of native grasses. However, other studies found that some invasive plants may suffer more from drought than native species, indicating that drought could also suppress alien plant invasion (Copeland et al, 2016;Kelso et al, 2020;LaForgia et al, 2018;Liu et al, 2017;Valliere et al, 2019;Werner et al, 2010).…”
Section: Introductionmentioning
confidence: 96%